Developing Halal Geotourism in Indonesia by Improving the Glob-al Muslim Travel Index (GMTI) Performace Using ESG Perspec-tive - Bening Kalimasada Aura Keindahan (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2023)
Indonesia is well-known for its geotourism, offering various geological and geomorphologic attractions and destinations. Geotourism in Indonesia fosters environment, heritage, aesthetics, culture, and the community's well-being. In addition, Indonesia ranked second in the Global Muslim Travel Index (GMTI) Rankings by Crescent Rating. Indonesia performs well in providing prayer places, having free faith restrictions, increasing stakeholder awareness, and delivering general safety. However, there must be a comprehensive integration between these two excellences (geotourism and halal tourism). There are only a few insights about combining halal tourism and geotourism. Geotourism represents the role of the environment, not only being of service to humans but also worshipping God. Unfortunately, some geotourism places are prone to impropriety, do not provide a place for prayer, and have leisurely access to meals forbidden by Islamic law (haram). One of the main factors of this is the role of the stakeholders. This study collects secondary data to be analyzed by qualitative analysis to develop halal geotourism in Indonesia. Halal geotourism needs to adopt the excellent accomplishment of Indonesia in the Global Muslim Travel Index (GMTI) and utilize the emerging Environment, Social, and Governance (ESG) trend. ESG can be the consideration in planning the strategy of making immigration for international tourists efficient, raising stakeholder awareness, ensuring safety, and providing Muslim-friendly facilities in geotourism. ESG perspective can be incorporated in bettering the lousy performance in GMTI, such as providing connectivity, strengthening communication proficiency, continuously creating innovations, implementing sustainability, and presenting unique experiences. As a result, halal geotourism with the ESG as the base perspective will accelerate geotourism development in Indonesia and help achieve halal tourism development goals.